ENCEPHALITIS: PARENCHYMAL LEUCOCYTES IN INFECTIOUS, IMMUNE AND UNKNOWN CAUSE. Issue 12 (15th November 2016) - Daramola, O; Rathi, N; Michael, BD; Griffiths, MJ; Moxham, N; Benjamin, L; Crooks, D; Solomon, T
Abstract : Introduction: The spectrum of encephalitis, a condition of brain inflammation and leucocyte infiltration, is expanding. Modern peripheral testing has resulted in fewer brain-biopsies. Consequently, our understanding of leucocyte-subsets driving inflammation is poorly understood. Methods: The Walton Centre Brain-Bank was screened over 10 years, identifying all cases of biopsy and post-mortem tissue with encephalitis. Tissue underwent haemotoxylin/eosin stain, and immunohistochemical analysis for CD3, CD4, CD8, CD68, and CD79a. The immediate perivascular and surrounding parenchymal infiltrate quantitatively assessed. Results: Of nine cases, two were herpes simplex virus (HSV), four immune-mediated, and three of unknown cause. In comparison to those of unknown cause, HSV had a greater proportion of CD4 and CD68 positive cells in the perivascular and immediate parenchyma respectively (p=0.007 and p=0.004). Neutrophils were only identified in HSV. Immune-mediated cases generally had a limited inflammatory infiltrate, similarly to unknown cases. Although one paraneoplastic case had a marked inflammatory infiltrate, including CD8 positive cells. Conclusions: Our study describes potentially important differences in the relative leucocyte populations in the parenchyma of patients with encephalitis, which may have diagnostic and therapeutic implications. Further studies are planned to distinguish invading macrophage/monocytes from resident microglia in a transgenic murine model.